Kur'an'da Cehalet Kavramı - Yilmaz, M. Faik (Dinî araştırmalar, 2003)
In this study we aim to discuss the meaning of the concept of “Jahale” (Ignorance) in Koran. In literary meaning, Ignorance (Jahl) mean is oppsite of Know and theJahl’s mean is doing something without as ignorant. But the mean of this concept in Koran is something more. It is a personal situation no thinking about the universe around him and about himself. We find the “Ignorance" concept in Koran 24 times, in different using. Etimologic and semantic meaning is another target of this study. The “Ignorance”, is a period of Pre Islamic time. Because of polytheistic life Islamic sources call this period “Jahale”. We classificated the Koranic statement of “Ignorance" in four categories